Caveolin-1 Impacts on TGF-β Regulation of Metabolic Gene Signatures in Hepatocytes - Han, Mei; Nwosu, Zeribe Chike; Piorońska, Weronika; Ebert, Matthias Philip; Dooley, Steven; Meyer, Christoph (Frontiers in Physiology, 2020)
Caveolin-1 (CAV1) is a membrane protein associated with metabolism in various cell types. The transforming growth factor beta (TGF-β) is a pro-fibrogenic cytokine in the liver, but its metabolic gene signatures remain unclear to date. We have previously shown that CAV1 alters TGF β signaling and blocks its pro-apoptotic function. Here, we defined TGF-β-induced metabolic gene signatures in hepatocytes, and assessed whether CAV1 abundance impacts on TGF-β control of those metabolic genes. Microarray analyses of primary hepatocytes after CAV1 knockdown and TGF-β stimulation (48 h) showed differential expression of 4224 genes, of which 856 are metabolic genes (adjusted p<0.001). Functional annotation analysis revealed that TGF-β mainly suppress metabolic gene network, including genes involved in glutathione-, cholesterol-, fatty acid-, and amino acid metabolism. TGF-β also upregulated several genes related to glycan metabolism and ion transport. In contrast to TGF-β effects, CAV1 knockdown triggered the upregulation of metabolic genes. Immortalized mouse hepatocytes (AML12 cells) were used to validate the gene changes induced by TGF-β stimulation and CAV1 knockdown. Noteworthy, of the TGF-β metabolic target genes, CAV1 modulated the expression of 228 (27%). In conclusion, we present several novel metabolic gene signature of TGF-β in hepatocytes and show that CAV1 abundance alters almost a third of these genes. These findings could enable a better understanding of TGF-β function in normal and diseased liver conditions, especially where differential CAV1 level is implicated.